Prediction of reaction rate constants of hydroxyl radical with chemicals in water. (18th December 2020) - Yu, Xinliang; Liu, Jun
Abstract: The rate constants ( k OH ) of the reactions between organic micropollutants with hydroxyl radical (OH) in aqueous systems are an important parameter to evaluate the persistence of organic compounds in the environment. In this paper, a support vector machine (SVM) model based on five descriptors was built to predict the reaction rate constants (log K = (log k OH )/ M W ). The quantitative structure–activity relationship (QSAR) model of log K was obtained from a training set (600 compounds) and validated with a test set (395 compounds). The coefficients of determination R 2 of the training and test sets are 0.923 and 0.925, respectively. The results suggest that the SVM model developed in this work possesses satisfactory prediction ability. Practitioner points: The rate constants of the reactions of organic micropollutants with OH in aqueous systems were investigated. SVM model was established for the reaction rate constants (log K = (log k OH )/ M W ). Only five molecular descriptors were used to predict 995 log K . A large data set was used for the test set (395 compounds). Abstract : A support vector machine model was built to predict the reaction rate constants (log K = (log k OH )/ M W ) of the reactions between organic micropollutants with hydroxyl radical (OH) in aqueous systems.